Garlic revisited: antimicrobial activity of allicin-containing garlic extracts against Burkholderia cepacia complex. - Daynea Wallock-Richards; Catherine J Doherty; Lynsey Doherty; David J Clarke; Marc Place; John R W Govan; Dominic J Campopiano (PLoS ONE, 2014)
The antimicrobial activities of garlic and other plant alliums are primarily based on allicin, a thiosulphinate present in crushed garlic bulbs. We set out to determine if pure allicin and aqueous garlic extracts (AGE) exhibit antimicrobial properties against the Burkholderia cepacia complex (Bcc), the major bacterial phytopathogen for alliums and an intrinsically multiresistant and life-threatening human pathogen. We prepared an AGE from commercial garlic bulbs and used HPLC to quantify the amount of allicin therein using an aqueous allicin standard (AAS). Initially we determined the minimum inhibitory concentrations (MICs) of the AGE against 38 Bcc isolates; these MICs ranged from 0.5 to 3% (v/v). The antimicrobial activity of pure allicin (AAS) was confirmed by MIC and minimum bactericidal concentration (MBC) assays against a smaller panel of five Bcc isolates; these included three representative strains of the most clinically important species, B. cenocepacia. Time kill assays, in the presence of ten times MIC, showed that the bactericidal activity of AGE and AAS against B. cenocepacia C6433 correlated with the concentration of allicin. We also used protein mass spectrometry analysis to begin to investigate the possible molecular mechanisms of allicin with a recombinant form of a thiol-dependent peroxiredoxin (BCP, Prx) from B. cenocepacia. This revealed that AAS and AGE modifies an essential BCP catalytic cysteine residue and suggests a role for allicin as a general electrophilic reagent that targets protein thiols. To our knowledge, we report the first evidence that allicin and allicin-containing garlic extracts possess inhibitory and bactericidal activities against the Bcc. Present therapeutic options against these life-threatening pathogens are limited; thus, allicin-containing compounds merit investigation as adjuncts to existing antibiotics.